2021
DOI: 10.1128/spectrum.00735-21
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Protein Destabilizes Microvascular Homeostasis

Abstract: SARS-CoV-2 causes complex effects on microvascular homeostasis that potentially contribute to organ dysfunction and coagulopathies. SARS-CoV-2 binds to, and causes downregulation of angiotensin converting enzyme 2 (ACE2) on cells that it infects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Further, S protein disrupted human cardiac pericytes function and triggered increased production of proapoptotic factors in pericytes, causing endothelial cells death [79]. In support of this, administration of the S protein promoted dysfunction of human endothelial cells as evidenced by, for example, increased expression of the von Willebrand factor [80]. Other reports indicate that S1 can directly induce coagulation by competitive binding to both soluble and cellular heparan sulfate/heparin (an anticoagulant) [81][82][83][84], while cell-free hemoglobin, as a hypoxia counterbalance, cannot attenuate disruption of endothelial barrier function, oxidative stress, or inflammatory responses in human pulmonary arterial endothelial cells exposed to S1 [85].…”
Section: Box 2 Other Types Of Covid-19 Vaccinementioning
confidence: 96%
“…Further, S protein disrupted human cardiac pericytes function and triggered increased production of proapoptotic factors in pericytes, causing endothelial cells death [79]. In support of this, administration of the S protein promoted dysfunction of human endothelial cells as evidenced by, for example, increased expression of the von Willebrand factor [80]. Other reports indicate that S1 can directly induce coagulation by competitive binding to both soluble and cellular heparan sulfate/heparin (an anticoagulant) [81][82][83][84], while cell-free hemoglobin, as a hypoxia counterbalance, cannot attenuate disruption of endothelial barrier function, oxidative stress, or inflammatory responses in human pulmonary arterial endothelial cells exposed to S1 [85].…”
Section: Box 2 Other Types Of Covid-19 Vaccinementioning
confidence: 96%
“…Many researchers have reported that systemic pathological events (excessive immune response, hyper-inflammation, and release of proinflammatory cytokines and chemokines) in COVID-19 infection trigger macro and microvascular thrombosis [20][21][22]. Additionally, the recruitment and activation of leukocytes and platelets result in the progression of coagulopathy via intravascular generation of thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…Several experts have suggested that SARS-CoV-2 replicates in endothelial cells; this replication might be further promoted if the endothelium has already been damaged [122] . The virus spike protein's disorganising effects on the microvasculature were reviewed recently [123] . Interestingly, autopsy material indeed showed early lesions in capillaries and microthrombi in arterioles; as well as some damage to larger vessels [124] .…”
Section: Putative Mechanisms Underlying Met's Protective Effectsmentioning
confidence: 99%